Disturbance Observer-Based Adaptive Control of Hypersonic Vehicles with Constrained Actuators - Guan Wang; Li Li; Weihua Li; Huajun Zhou; Changbo Ma; Hongwei Xia (International Journal of Aerospace Engineering)
This study investigates an adaptive controller for the flexible air-breathing hypersonic vehicles (AHVs) subject to external disturbances and actuator constraints. The combination of nonlinear disturbance observer and adaptive mechanism is exploited to design an adaptive controller for each subsystem. For the velocity subsystem, an auxiliary system is employed to handle the scramjet input saturation issue. For the altitude subsystem, the magnitude/rate constraints and the dynamics of aerodynamic control surfaces are addressed by the control allocation module. Simulations show the effectiveness of the proposed control.